Membangun Hubungan Komisi Yudisial Dengan Mahkamah Agung Yang Ideal - Juanda; Ogiandhafiz Juanda (Faculty of Law, Universitas Bhayangkara Jakarta Raya, 2021)
The phenomenon of the relationship between the Judicial Commission (KY) and the Supreme Court (MA) has had its ups and downs, and there are still many misinterpretations, as well as no common paradigm. As a result, if left unchecked, it could have a wide-ranging impact on law enforcement and justice in Indonesia's justice system. There are many aspects that need to be developed namely by establishing common paradigm and evaluating each party’s duties and authorities in order to achieve a harmonious relationship and strong synergy. Based on the problematic relationship between the two state institutions, the author is interested in studying and discussing